Self-Efficacy In Relation To Students’ Reading Comprehension (RETAIN, 2020)
Abstract In this globalization era, students must have the ability to read because reading is the key to student success in learning. Reading has become the language skills to be acquired by the students to support their learning. Reading is quite hard to do for some students because it needs concentration and a supporting environment. Nowadays, students are only read to find specific information and ignore the other information. Many different factors are influencing students in reading, such as students’ self-efficacy, the belief that people can do some tasks at different levels of knowledge and skills. It takes main roles in the academic achievement and reading comprehension of the students. Therefore, this article examines the relationship of self-efficacy and students’ reading comprehension. Keywords: reading comprehension, self-efficacy, reading self-efficacy